2003
DOI: 10.1359/jbmr.2003.18.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment of Incadronate Disodium Accumulates Microdamage but Improves the Trabecular Bone Microarchitecture in Dog Vertebra

Abstract: This study aimed to investigate the effect of long-term suppression of bone resorption by bisphosphonate on the microstructure, accumulation of microdamage, and mechanical properties of trabecular bone. Twentynine 1-year-old beagles (15 males, 14 females) were divided into three groups. The control group (CNT) was treated daily with vehicle, and the other two groups were treated with incadronate at a dose of 0.3 mg/kg/day (LOW) or 0.6 mg/kg/day (HIGH) orally for 3 years. After death, the second thoracic verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 51 publications
6
75
1
2
Order By: Relevance
“…(50) In support of this, several studies have suggested that long-term inhibition of bone turnover by bisphosphonates may result in increased microfracture accumulation and, in some cases, decreased bone strength. (51)(52)(53) At the dosing schedule used here, dasatinib treatment of normal rats decreased OC numbers and serum CTX-1 levels by 50%. In contrast, there were no changes in OB activity in dasatinib-treated animals, as determined by the serum markers osteocalcin and P1NP and by the dynamic measurements MS/BS Ã , BFR Ã , and MAR Ã , suggesting that bone turnover still may have been occurring.…”
Section: Discussionmentioning
confidence: 93%
“…(50) In support of this, several studies have suggested that long-term inhibition of bone turnover by bisphosphonates may result in increased microfracture accumulation and, in some cases, decreased bone strength. (51)(52)(53) At the dosing schedule used here, dasatinib treatment of normal rats decreased OC numbers and serum CTX-1 levels by 50%. In contrast, there were no changes in OB activity in dasatinib-treated animals, as determined by the serum markers osteocalcin and P1NP and by the dynamic measurements MS/BS Ã , BFR Ã , and MAR Ã , suggesting that bone turnover still may have been occurring.…”
Section: Discussionmentioning
confidence: 93%
“…Data from biomechanical tests performed on the vertebrae of beagle dogs treated with bisphosphonates [1][2][3][4] consistently indicate that there is a reduction in toughness. However, reports of bisphosphonate-induced changes in rib toughness have thus far been discordant [5,6].…”
Section: Discussionmentioning
confidence: 95%
“…Following one year of treatment at doses equivalent to or below those used to treat postmenopausal osteoporosis, bisphosphonates non-significantly reduced (-6 to -20%) vertebral bone toughness [1]; higher doses significantly reduced vertebral toughness (-21%) [2]. Bisphosphonate treatment for three years significantly reduced vertebral toughness compared to vehicle-treated controls at doses both equivalent to (-27%) and above (-30 to -40%) those used to treat patients with osteoporosis [3,4].…”
Section: Introductionmentioning
confidence: 95%
“…Although a number of studies have looked at the effects of bisphosphonates on trabecular bone biomechanics in large animals [50][51][52][53][54][55][56][57], we could find only two that looked specifically for differences in mechanical properties relative to density [49,58]. Neither of the studies observed significant changes in the relationships as a result of treatment.…”
Section: What Do We Know About Trabecular Bone Quality?mentioning
confidence: 86%